Choice Bundling Increases Valuation of Delayed Losses More Than Gains in Cigarette Smokers - Stein, Jeffrey S.; Brown, Jeremiah M.; Tegge, Allison N.; Freitas-Lemos, Roberta; Koffarnus, Mikhail N.; Bickel, Warren K.; Madden, Gregory J. (Frontiers in Behavioral Neuroscience, 2022)
Choice bundling, in which a single choice produces a series of repeating consequences over time, increases valuation of delayed monetary and non-monetary gains. Interventions derived from this manipulation may be an effective method for mitigating the elevated delay discounting rates observed in cigarette smokers. No prior work, however, has investigated whether effects of choice bundling generalize to reward losses. In the present study, an online panel of cigarette smokers (N=302), recruited using Ipsos and InnovateMR, completed assessments for either monetary gains or losses (randomly assigned). In Step 1, participants completed a delay-discounting task to establish Effective Delay 50 (ED50), or the delay required for an outcome to lose half of its value. In Step 2, participants completed three conditions of an adjusting-amount task, choosing between a smaller, sooner (SS) adjusting amount and a larger, later (LL) fixed amount. The bundle size (i.e., number of consequences) was manipulated across conditions, where a single choice produced either 1 (control), 3, or 9 consequences over time (ascending/descending order counterbalanced). The delay to the first LL amount in each condition, as well as the intervals between all additional SS and LL amounts (where applicable), were set to individual participants’ ED50 values from Step 1 to control for differences in discounting of gains and losses. Results from Step 1 showed significantly higher ED50 values (i.e., less discounting) for losses compared to gains (p<.001). Results from Step 2 showed that choice bundling significantly increased valuation of both LL gains and losses (p<.001), although effects were significantly greater for losses (p<.01). Sensitivity analyses replicated these conclusions. Future research should examine the potential clinical utility of choice bundling, such as development of motivational interventions that emphasize both the bundled health gains associated with smoking cessation and the health losses associated with continued smoking.